2010
DOI: 10.1016/j.clinph.2010.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing plasticity through repeated rTMS sessions: The benefits of a night of sleep

Abstract: Objective-Previous work has demonstrated that corticospinal facilitation from 20Hz repetitive transcranial magnetic stimulation (rTMS) was greater during a second rTMS session 24 hours after the first. We sought to determine whether such metaplasticity is dependent on a particular phase of the sleep-wake/circadian cycle.Methods-Twenty healthy participants received two sessions of 20 Hz rTMS over the hand motor cortex (M1) spaced 12 hours apart, either over-day or overnight.Results-Baseline corticospinal excita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 54 publications
0
15
1
Order By: Relevance
“…In the context of narcolepsy, regenerative therapies for the hypocretin system, which undergoes degeneration in narcolepsy, are worthy of attention and effort (102, 103). In addition, transcranial manipulation of the electrical activity of the cerebral cortex (ultimately the seat of fatigue-related deficits) for therapeutic intervention is fast becoming a reality (104, 105). …”
Section: Resultsmentioning
confidence: 99%
“…In the context of narcolepsy, regenerative therapies for the hypocretin system, which undergoes degeneration in narcolepsy, are worthy of attention and effort (102, 103). In addition, transcranial manipulation of the electrical activity of the cerebral cortex (ultimately the seat of fatigue-related deficits) for therapeutic intervention is fast becoming a reality (104, 105). …”
Section: Resultsmentioning
confidence: 99%
“…Other variables that might contribute to change test-retest reliability involving TMS, by influencing the basal level of neuronal activity, may include time of day (Sale et al, 2007), hormonal changes (e.g., menstrual cycle, post-menopause), level of anxiety or mood, sleep deprivation, or occult substance abuse (Rossi et al, 2009). For instance, Cohen et al (2010) found that TMS measures of plasticity can show significant diurnal changes, consistent with chronobiologic factors. Therefore, careful consideration of such factors in test-retest reliability studies is critical.…”
Section: Challenges and Advancements To Use Tms Measures Of Plasticitmentioning
confidence: 91%
“…Yet, this effect was not shown to improve working memory performance. Eventually, repeated, daily rTMS sessions might be needed to produce changes in plasticity [e.g., (63)] and lasting effects on cognition. On the other hand, Plewnia et al (64) showed that synchronous, bifocal rTMS can induce an increase of interregional EEG coherence, which may eventually have behavioral consequences.…”
Section: Tms Paradigms To Measure Cortical Function In Schizophreniamentioning
confidence: 99%